Medial Meniscus Posterior Root Repair Using a Transtibial Technique - Jarret M. Woodmass, M.D., F.R.C.S.C.; Rohith Mohan, B.A.; Michael J. Stuart, M.D.; Aaron J. Krych, M.D. (Arthroscopy Techniques, 2017)
The meniscal roots are critical in maintaining the normal shock absorbing function of the meniscus. If a meniscal root tear is left untreated, meniscal extrusion can occur rendering the meniscus nonfunctional resulting in degenerative arthritis. Two main repair techniques are described: (1) suture anchors (direct fixation) and (2) sutures pulled through a tibial tunnel (indirect fixation). Meniscal root repair using a suture anchor technique is technically challenging requiring a posterior portal and a curved suture passing device that can be difficult to manipulate within the knee. We present a technique for posterior medial meniscus root repair using 3 sutures (1 leader, 2 cinch), standard arthroscopy portals, and transtibial fixation. Overall, this technique simplifies a challenging procedure and allows for familiarity and efficiency.